2017
DOI: 10.1080/23273798.2017.1395467
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of spoken word production in semantic and phonological blocked cyclic naming

Abstract: The blocked cyclic naming paradigm has been increasingly employed to investigate the mechanisms underlying spoken word production. Semantic homogeneity typically elicits longer naming latencies than heterogeneity; however, it is debated whether competitive lexical selection or incremental learning underlies this effect. The current study manipulated both semantic and phonological homogeneity and used behavioural and electrophysiological measurements to provide evidence that can distinguish between the two acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 47 publications
4
36
0
Order By: Relevance
“…In this line, Barber and Carreiras (2005) and Caffarra, Janssen, and Barber (2014) found that gender disagreement in word pairs formed by a noun and an adjective elicited an “N400-type effect”: disagreeing words produced larger negative deflections as compaed to agreeing words. Wang et al (2018) reported similar findings in a bare noun production task in Mandarin Chinese, in which they manipulated the congruency of a lexico-syntactic classifier feature (comparable to grammatical gender). The results showed that the classifier incongruent condition elicited larger N400 effects in comparison to the classifier congruent condition.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In this line, Barber and Carreiras (2005) and Caffarra, Janssen, and Barber (2014) found that gender disagreement in word pairs formed by a noun and an adjective elicited an “N400-type effect”: disagreeing words produced larger negative deflections as compaed to agreeing words. Wang et al (2018) reported similar findings in a bare noun production task in Mandarin Chinese, in which they manipulated the congruency of a lexico-syntactic classifier feature (comparable to grammatical gender). The results showed that the classifier incongruent condition elicited larger N400 effects in comparison to the classifier congruent condition.…”
Section: Introductionmentioning
confidence: 72%
“…Thus, they propose that gender information would not be retrieved when agreement is not required. In contrast, some recent evidence suggests that this grammatical property also seems to be automatically activated during lexical access outside of a sentence context, that is, in the production of bare nouns (Alario, Ayora, Costa & Melinger, 2008; Cubelli, Lotto, Paolieri, Girelli & Job, 2005; Duràn & Pillon, 2011; Paolieri, Lotto, Leoncini, Cubelli & Job, 2011; see also Wang, Shao, Chen & Schiller, 2018, for a comparable lexico-syntactic classifier feature). Several theoretical proposals have been made to account for such findings, in terms of different dynamics of activation of grammatical gender information.…”
Section: Introductionmentioning
confidence: 99%
“…Using blocked cyclic naming, Janssen, Carreiras, and Barber (2011) found an effect in this window, with related blocks producing smaller negative amplitudes than unrelated blocks (Janssen, Hernández-Cabrera, van der Meij, & Barber, 2015;Wang, Shao, Chen, & Schiller, 2018). In a PWI paradigm comparing close and distant categorically related distractors to unrelated ones, Rose et al (2019) found a lower amplitude associated with the closely related compared to unrelated distractors.…”
Section: Electrophysiological Studiesmentioning
confidence: 93%
“…But this late effect might very well reflect the top-down effect of the frontally mediated "booster" assumed in incremental learning models (Oppenheim et al, 2010). Similarly, Wang et al (2018) claimed that their findings were evidence against the incremental learning model because they took the divergence of related vs. unrelated conditions at around 200 ms to represent lexical selection, and incremental learning was supposed to have its effect before lexical selection, i.e., during the mapping of semantic features to lexical items. But this claim is again based on an assumption derived from a serial model with competitive selection, the problems with which have been laid out in this and the previous point.…”
Section: Deriving Theoretical Perspectives From Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation